The high-rise private eyes : the case of the sleepy sloth - Rylant, Cynthia (Greenwillow Books, 2002)
While having a picnic on the docks, animal detectives Bunny and Jack meet a dog whose one and only lawn chair is missing, and they set out to solve the case.